Design, synthesis, docking, ADMET profile, and anticancer evaluations of novel thiazolidine‐2, 4‐dione derivatives as VEGFR‐2 inhibitors. Issue 7 (31st March 2021) - El‐Adl, Khaled; Sakr, Helmy; El‐Hddad, Sanadelaslam S. A.; El‐Helby, Abdel‐Ghany A.; Nasser, Mohamed; Abulkhair, Hamada S.
Abstract: The anticancer activity of novel thiazolidine‐2, 4‐diones was evaluated against HepG2, HCT‐116, and MCF‐7 cells. Among the tested cancer cell lines, HCT‐116 was the most sensitive one to the cytotoxic effect of the new derivatives. In particular, compounds 18, 11, and 10 were found to be the most potent derivatives among all the tested compounds against the HepG2, HCT‐116, and MCF‐7 cancer cell lines, with IC50 values ranging from 38.76 to 53.99 µM. The most active antiproliferative derivatives (7 –14 and 15 –19 ) were subjected to further biological studies to evaluate their inhibitory potentials against VEGFR‐2. The tested compounds displayed a good‐to‐medium inhibitory activity, with IC50 values ranging from 0.26 to 0.72 µM. Among them, compounds 18, 11, and 10 potently inhibited VEGFR‐2 at IC50 values in the range of 0.26–0.29 µM, which are nearly three times that of the sorafenib IC50 value (0.10 µM). Although our derivatives showed lower activities than the reference drug, they could be useful as a template for future design, optimization, adaptation, and investigation to produce more potent and selective VEGFR‐2 inhibitors with higher anticancer analogs. The ADMET profile showed that compounds 18, 11, and 10 do not violate any of Lipinski's rules and have a comparable intestinal absorptivity in humans. Also, the new derivatives could not inhibit cytochrome P3A4. Unlike sorafenib and doxorubicin, compounds 18, 11, and 10 are expected to have prolonged dosing intervals. Moreover, compounds 10 and 18 displayed a wide therapeutic index and higher selectivity against cancer cells as compared with their cytotoxicity against normal cells. Abstract : The anticancer activity of novel thiazolidine‐2, 4‐diones was evaluated against HepG2, HCT‐116, and MCF‐7 cells. Compounds 18, 11, and 10 were found to be the most potent derivatives, with IC50 values ranging from 38.76 to 53.99 µM. Compounds 18, 11, and 10 also potently inhibited VEGFR‐2 at IC50 values in the range of 0.26–0.29 µM. They do not violate any of Lipinski's rules and have a comparable intestinal absorptivity in humans.